The current status of emergency contraception use in reproductive-aged Korean women: a population-based internet survey - Lee, You Min; Kim, Sung Eun; Choi, DooSeok; Lee, Dong-Yun (Frontiers in Endocrinology, 2023)
Objective: This study was conducted to assess the current status of emergency contraception (EC) use in reproductive-aged Korean women. Materials and Methods: This study utilized a population-based, cross-sectional online survey using a self-completed questionnaire in women aged 20¬–44 years who had visited a clinic in the previous six months for contraception counseling. Reason for use, anxiety, and counseling for further contraception at EC use were analyzed according to age, history of childbirth, and contraceptive failure in EC users. Results: Among 1,011 respondents, 461 (45.6%) had experience with EC use. Younger age, need for EC due to inadequate contraception, and high anxiety were highly prevalent among EC users. However, women in the 20s were less likely to get counseling for further contraception at EC use. Additionally, the proportions of women who used EC due to inadequate contraception during sexual intercourse and who experienced high anxiety were lower among women who had a history of childbirth. Women who had a history of contraceptive failure worried less about EC use. Conclusions: Our findings offer insight for developing and improving individualized strategies for adequate contraception, especially in young Korean EC users.